Tardigrade diversity around Syowa Station, Dronning Maud Land in East Antarctica - Tsujimoto, Megumu; Suzuki, Atsushi C.; Nakai, Ryosuke; Imura, Satoshi (2018)
The Ninth Symposium on Polar Science/Ordinary sessions: [OB] Polar biology, Wed. 5 Dec. / Entrance Hall (1st floor), National Institute of Polar Research conference object